Exploration of fecal microbiota in newly diagnosed patients with inflammatory bowel disease using shotgun metagenomics - Orejudo, Macarena; Gómez, Manuel J.; Riestra, Sabino; Rivero, Montserrat; Gutiérrez, Ana; Rodríguez-Lago, Iago; Fernández-Salazar, Luis; Ceballos, Daniel; Benítez, José Manuel; Aguas, Mariam; Bastón-Rey, Iria; Bermejo, Fernando; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionDysbiosis is a key mechanism in inflammatory bowel disease (IBD) pathophysiology. Previous microbiota studies in IBD generally have involved patients treated with immunosuppressive agents, which can affect the results. We aimed to elucidate the fecal microbiota composition in newly diagnosed treatment-naïve IBD patients.MethodsMicrobiota from stool samples were investigated using shotgun metagenomics sequencing and subsequent bioinformatics analysis.ResultsA total of 103 patients with Crohn's disease (CD), 144 with ulcerative colitis (UC), and 49 healthy controls (HC) were included. CD patients had significantly lower species-level diversity than those with UC and HC. CD subgroups with Ileocolonic location and stricturing behavior showed reduced diversity compared to HC. A negative correlation was observed between endoscopic severity and microbial diversity in CD patients. UC patients had similar microbial diversity to HC, which was unaffected by disease activity. Taxonomic abundance analysis revealed a tendency towards a higher relative abundance of Escherichia coli and a lower relative abundance of Faecalibacterium prausnitzii in IBD patients compared to HC. However, the most significant differences in these patients compared to HC were observed in less abundant species, such as Toxoplasma gondii, Gemella morbillorum, and several species of the Adlercreutzia genera. Functional analysis in these patients highlighted changes in carbohydrate and nucleotide pathways.DiscussionOur data suggest that newly diagnosed CD patients show significant microbiota composition disparities compared to UC patients and HC. Microbiota differences in these patients are linked to dysbiosis, characterized by a reduction in beneficial genera such as Gemella and Adlercreutzia, and a rise in pathogenic species.